Teachers and students Technological Awareness and Classroom Practices - Dr.Maksal Minaz,; Dr. Mehwiah Habib,; Mrs. Ghazala Naheed Baig, (Dialogue Social Science Review (DSSR), 2024)
The study aim was to investigate the 21st century technological awareness of teachers and the classroom practices of students at secondary level. The research objectives were; to find out the awareness of the 21st century school teachers regarding the technological literacy and to co-relate the 21st century technological awareness of teachers and the classroom practices of students. For the achievement of research objectives number of two hundred and eighty two (282) secondary school teachers and three hundred eighty (380) secondary school students (class 10th) were selected through Raosoft online sample size calculator for the purpose of data collection. Self-developed technological Literacy Questionnaire (TLQ) was validated and the reliability was found to be Cronbach’s alpha α = .938. Analysis of the data was done through SD, t-test, Pearson Product Moment Correlation, at the 0.05 level of significance. The findings revealed that 21st century teaches possess the necessary technological experiences to incorporate and utilize computers through teaching and learning, ultimately leading to improved student performance in the classroom. The results revealed strong correlation was found between technological competencies of teachers and the classroom performance of students, with a significance level of 0.01. It was concluded that both secondary school teachers and the students possess a high level of technological experiences, which positively impact the performance of student at secondary level. Consequently, it was recommended that the government take substantial measures to enhance the technological skills of 21st century teachers and provide the regular training sessions to improve the classroom performance of student.